2021
DOI: 10.1017/s104795112100264x
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of atrial septal defect with deficient posterior-inferior or inferior vena cava rim under echocardiography only: a feasibility and safety analysis

Abstract: Background: The safe closure of atrial septal defect with deficient posterior-inferior or inferior vena cava rim is a controversial issue. Few studies have been conducted on the closure of atrial septal defect with deficient posterior-inferior or inferior vena cava rim without fluoroscopy. This study evaluated the feasibility and safety of echocardiography-guided transcatheter closure of atrial septal defect with deficient posterior-inferior or inferior vena cava rim. Methods: The data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, our study supports that nowadays transcatheter ASD closure with TTE and fluoroscopy guidance and balloon sizing is safe and effective. However, in some recent studies, TTE or TEE-guided transcatheter ASD closure without fluoroscopy guidance has been shown to be feasible, safe, and effective in children and adults (30)(31)(32)(33). Also, It has been reported that successful transcatheter ASD closure can be performed with expert operators without balloon sizing under the guidance of fluoroscopy and TTE in suitable adult cases (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our study supports that nowadays transcatheter ASD closure with TTE and fluoroscopy guidance and balloon sizing is safe and effective. However, in some recent studies, TTE or TEE-guided transcatheter ASD closure without fluoroscopy guidance has been shown to be feasible, safe, and effective in children and adults (30)(31)(32)(33). Also, It has been reported that successful transcatheter ASD closure can be performed with expert operators without balloon sizing under the guidance of fluoroscopy and TTE in suitable adult cases (34).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the deficient posteroinferior rim, in their study, Cao et al were able to treat patients with less than 5 mm rims using devices up to 6 mm larger than the maximum measured diameter, and they monitored the rims using TTE and TEE simultaneously [64]. On the contrary, in a study by Huang, the same success rate was achieved in both groups with sufficient and deficient posteroinferior or inferior vena cava rim [65]. Occlusion by percutaneous means may be difficult in large defects with floppy posterior or posteroinferior edges [62,66,67].…”
Section: Challenges and Limitationsmentioning
confidence: 99%